2018
DOI: 10.1021/acs.biochem.7b01005
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Hydrogen-Bond Network and Impaired ATPase Activity in an Hsc70 Cysteine Mutant

Abstract: The ATPase domain of members of the 70 kDa heat shock protein (Hsp70) family shows a high degree of sequence, structural, and functional homology across species. A broadly conserved residue within the Hsp70 ATPase domain that captured our attention is an unpaired cysteine, positioned proximal to the site of nucleotide binding. Prior studies of several Hsp70 family members show this cysteine is not required for Hsp70 ATPase activity, yet select amino acid replacements of the cysteine can dramatically alter ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 78 publications
(244 reference statements)
1
10
0
Order By: Relevance
“…Based on these observations, we suggest that they might affect ATP hydrolysis by indirectly altering the bonds formed and the secondary movements of the molecule. This prediction is indirectly supported by the finding that C17, which does not bind directly to ATP, alters the ATPase activity of Hsp70 by disrupting the hydrogen-bond network within the active site [15]. Differently, the F592S mutation, which is located at the lid subdomain of the SBD and showed an increase in ADP-binding entropy [3], may alter the conformation or movement of the lid subdomain and thus indirectly affect ATP hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, we suggest that they might affect ATP hydrolysis by indirectly altering the bonds formed and the secondary movements of the molecule. This prediction is indirectly supported by the finding that C17, which does not bind directly to ATP, alters the ATPase activity of Hsp70 by disrupting the hydrogen-bond network within the active site [15]. Differently, the F592S mutation, which is located at the lid subdomain of the SBD and showed an increase in ADP-binding entropy [3], may alter the conformation or movement of the lid subdomain and thus indirectly affect ATP hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the conserved Cys17 in the ATPase domain of the cytosolic chaperone protein, Hspa8, was continually oxidized (Cluster 7). As the perpetual oxidation of the conserved cysteine in the ER chaperone, Hspa5, has been shown to enhance chaperone function and ER homeostasis, the perpetual oxidation of Hspa8 indicates a potential function in cytosolic protein homeostasis during ISO-induced cardiac hypertrophy. ,, …”
Section: Resultsmentioning
confidence: 99%
“…As the perpetual oxidation of the conserved cysteine in the ER chaperone, Hspa5, has been shown to enhance chaperone function and ER homeostasis, the perpetual oxidation of Hspa8 indicates a potential function in cytosolic protein homeostasis during ISOinduced cardiac hypertrophy. 21,22,38 The stoichiometry is an important feature of PTM and can be calculated by comparing the abundance of a modified form with all forms of a site of interest. Integrating the temporal patterns of total cysteine abundance and reversible cysteine O-PTM further reveals the comprehensive regulation of cysteine O-PTM stoichiometry.…”
Section: Integrated Temporal Profiles Of Cysteine O-ptm In Hypertroph...mentioning
confidence: 99%
“…NEM-treated Ssa1 displayed altered trypsinization profiles and intrinsic tryptophan fluorescence indicative of structural deformation within the NBD 34 . In human Hsc70, it was found that modification of nucleotide pocket-facing C17 displaced a catalytic magnesium ion that is crucial for nucleotide hydrolysis by increasing the distance of that magnesium from several interacting residues 52 . These results are also consistent with previous data that methylene blue oxidizes cysteines 267 and 306 in the stress-inducible human Hsp70, resulting in reduced ATP binding and hydrolysis 30 .…”
Section: Discussionmentioning
confidence: 99%